Cytokines in Mycoplasma hyorhinis-Induced Arthritis in Pigs Bred Selectively for High and Low Immune Responses - Jayagopala Reddy, N. R. (American Society for Microbiology, 2000)
Yorkshire pigs were bred selectively for high and low immune responses (H and L pigs, respectively) based on multiple antibody (Ab) and cell-mediated immune response traits. In a previous experiment, generation 4 (G4) pigs of each line were infected with Mycoplasma hyorhinis. High responders had a more rapid and higher Ab response and less polyserositis, but arthritis was more severe in H pigs than in L pigs. To test the hypothesis that line differences were attributable to differential expression of cytokines, M. hyorhinis infection was induced in pigs of G8. Arthritis was more severe clinically (P, ≤0.05) and postmortem (P, ≤0.001) when M. hyorhinis CFU were more numerous in synovial fluid (SF) of H pigs than of L pigs (P, ≤0.03). In H pigs but not L pigs, CFU and lesion scores were correlated positively. In H pigs, infection increased the frequency of expression of mRNAs for interleukin-8 (IL-8), IL-10, and tumor necrosis factor alpha (TNF-α) in mononuclear cells from synovial membranes (SM). In L pigs, IL-1α, IL-6, IL-10, and TNF-α mRNAs were increased in frequency of expression. The quantity of the cytokine message for IL-6 was increased in infected H pigs. For L pigs, infection increased the cytokine message for IL-1α, IL-6, IL-10, and TNF-α. IL-6 in SM and gamma interferon (IFN-γ) in SF were produced at a higher copy number in H pigs than in L pigs after infection. For H pigs, there were no positive rank correlations between lesion or CFU scores and cytokines. For L pigs, IL-1α, IL-8, IL-10, and TNF-α in SM correlated with CFU, while IL-6, TNF-β, and IFN-γ in SF correlated with CFU. Lesion score in L pigs correlated with IL-1α in SF. While these results indicate that H and L pigs differ in the cytokine response to M. hyorhinis infection, they do not confirm a characteristic cytokine response in association with the relative susceptibility to infection and arthritis observed in H pigs.